Phosphatidylinositol 3‐phosphates—at the interface between cell signalling and membrane traffic. (17th February 2016) - Marat, Andrea L; Haucke, Volker
Abstract: Phosphoinositides (PIs) form a minor class of phospholipids with crucial functions in cell physiology, ranging from cell signalling and motility to a role as signposts of compartmental membrane identity. Phosphatidylinositol 3‐phosphates are present at the plasma membrane and within the endolysosomal system, where they serve as key regulators of both cell signalling and of intracellular membrane traffic. Here, we provide an overview of the metabolic pathways that regulate cellular synthesis of PI 3‐phosphates at distinct intracellular sites and discuss the mechanisms by which these lipids regulate cell signalling and membrane traffic. Finally, we provide a framework for how PI 3‐phosphate metabolism is integrated into the cellular network. Abstract : Phosphatidylinositol 3‐phosphates exhibit different effects depending on their subcellular localization. This review discusses their roles as well as the mechanisms that control their spatiotemporal biosynthesis and turnover.